Factors Affecting Technical Efficiency in Potato Farming: A Data Envelopment Analysis (DEA) Study in East Java, Indonesia - Riska Elsa Rianty Sinaga; Nuhfil Hanani; Dwi Retno Andriani (Universitas Muhammadiyah Malang, 2024)
Potato farming has a crucial role in promoting the agricultural sector of East Java, Indonesia, with significant consequences for regional economic growth and acting as the main source of income for farmers. However, the primary challenge that potato farmers face involves improving production efficiency in order to strengthen the sustainability and competitiveness of the agricultural industry. This study aims to analyze the technical efficiency of potato farming in East Java and identify the factors affecting this efficiency. The study focuses on the areas of Sumberberantas and Wonokerso in East Java, which serve as key centers for growing potatoes. The study includes a group of 82 farmers as respondents, with 40 from Sumberberantas and 42 from Wonokerso. Data Envelopment Analysis (DEA) is a method that systematically examines levels of technical efficiency. It is complimented by Tobit Regression Analysis, which assists in identifying the relevant elements affecting efficiency. The findings indicate that the average technical efficiency score is 0.840, suggesting that farmers have the potential to increase their efficiency by up to 16%. Gender and land area for potato farming are identified as crucial factors affecting technical efficiency, while age, education, and farming experience have no effect.